(untitled) (Journal of Mathematics Mechanics and Computer Science, 2015)
Given paper describes the new instrument of multicluster organization of distributed computations and gives its detailed description using key components and implementation issues as autonomous program module. The purpose of given module and attached broker is to provide framework and execution environment of parallel applications in multicluster computational environments for conducting computational experiments with applied problems of the numerical modeling of the filtration theory merging into unified computational complex several computational clusters. Therefore, built unified communication environment becomes multicluster distributed computational system for solving large scale сomputational problems. Library part of the module, used in program code of applied problems, is MPJ-Express framework add-on and developed using Java programming language. Using Java in developed add-on allows integration into wide range of computer platforms starting form standard desktop Windows systems and finishing with large Linux clusters, which ensures general rule of the ubiquitous computing. The work presented in given article is a part of grant funding project from Kazakhstan government.